Ethical Issues in Care and Treatment of Neuronal Ceroid Lipofuscinoses (NCL)–A Personal View - Kohlschütter, Alfried (Frontiers in Neurology, 2021)
Neuronal Ceroid Lipofuscinoses (NCL), a group of genetic neurodegenerative disorders mainly affecting brain and retinas, raise difficult questions for physicians and other professionals in research, pharmaceutical industry and public health. Ethical problems in medicine can neither be solved by rational deliberation nor by following formal rules. Two topics of ethical issues in the field of NCL are presented. One group relates to the care of individual patients and centers on a life with early dementia and death. Advanced care planning and the use of life-prolonging measures require challenging assumptions in the best interest of a patient. A second group of questions relates to impressive novel putative causal therapies, such as enzyme replacement for CLN2 disease, which may be only disease-modifying and carry the risk of changing a deadly disease of short duration into one with prolonged survival and poor quality of life. The wish for better therapeutic interventions in lifelimiting diseases has to take such risks, but more experience is needed before definite conclusions can be drawn. The appropriateness of presymptomatic screening for a severe disease must be carefully evaluated to avoid disastrous experiences, such as with the rash start of newborn screening for Krabbe disease. The ethical issues described in the article reflect the experience of a pediatrician who has studied clinical and research questions in NCL for four decades. They should alert various professionals to the necessity of taking own decisions in situations that are caused by NCL and similar rare progressive brain diseases of young persons.